Spatial Decorrelation of SBAS Satellite Error Corrections in the Korean Peninsular - Jang, Jaegyu; So, Hyoungmin; Lee, Kihoon; Park, Jun-Pyo (International journal of aeronautical and space sciences, 2016)
The characteristics of the SBAS satellite orbit and clock corrections are highly affected by the narrow network size in the Korean peninsula, which is expected to have an important role in the future dual frequency SBAS. The correlation between satellite corrections can be analyzed in terms of the spatial decorrelation effect which should be analyzed to keep the service area as wide as possible. In this paper, the characteristics of satellite error corrections for the potential Korean dual frequency SBAS were analyzed, and an optimal filter design approach is proposed to maximize the service area. KCI Citation Count: 1